2005
DOI: 10.1002/hep.20568
|View full text |Cite
|
Sign up to set email alerts
|

No relevant effect of ursodeoxycholic acid on cytochrome P450 3A metabolism in primary biliary cirrhosis

Abstract: Induction of cytochrome P450 3A (CYP3A) has been suggested as a mechanism of action of ursodeoxycholic acid (UDCA) in cholestasis. CYP3A is of key importance in human drug metabolism, being involved in presystemic extraction of more than 50% of all drugs currently available and of various endogenous compounds. Therefore, we compared the induction potential of UDCA with that of the prototypical inducer rifampicin in a human model study with the CYP3A substrates budesonide and cortisol. Twelve patients with earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 49 publications
6
30
0
Order By: Relevance
“…The highly effective combination is provided by CYP3A, SULT2A1, MRP2 and MDR1 at both intestinal and hepatic level. An excellent example of the efficacy of this system was provided by Dilger et al (2005) 2 who administered a single dose of the synthetic corticosteroid budesonide to healthy human volunteers and charted its concentration in peripheral blood. Remarkably, following a 5-day course of rifampicin which is a known inducer of CYP3A, virtually no budesonide could be detected in the systemic circulation following an oral dose.…”
Section: Coordinated Biliary Defence Mechanismsmentioning
confidence: 99%
“…The highly effective combination is provided by CYP3A, SULT2A1, MRP2 and MDR1 at both intestinal and hepatic level. An excellent example of the efficacy of this system was provided by Dilger et al (2005) 2 who administered a single dose of the synthetic corticosteroid budesonide to healthy human volunteers and charted its concentration in peripheral blood. Remarkably, following a 5-day course of rifampicin which is a known inducer of CYP3A, virtually no budesonide could be detected in the systemic circulation following an oral dose.…”
Section: Coordinated Biliary Defence Mechanismsmentioning
confidence: 99%
“…Concentrations of budesonide, 6β-hydroxybudesonide, and 16α-hydroxyprednisolone in plasma and urine were determined by validated liquid chromatography tandem mass spectrometry according to the principles of Good Laboratory Practice as described previously [12]. The lower limits of quantification in plasma (urine) were 0.1 ng/ml (0.5 ng/ml) for budesonide and 6β-hydroxybudesonide, and 0.5 ng/ml (2 ng/ml) for 16α-hydroxyprednisolone.…”
Section: Methodsmentioning
confidence: 99%
“…In otherwise healthy gallstone patients undergoing cholecystectomy, rifampicin induced upregulation of UGT1A1 and MRP2 facilitating bilirubin elimination and increased CYP3A4 expression facilitating detoxification of bile acids 72 . Consistent with this, Dilger et al showed that in patients with early stage PBC and healthy controls, rifampicin markedly induced CYP3A metabolism as assessed by pharmacokinetic profiling of budesonide and its phase 1 metabolites in plasma and urine and urinary 6β-hydroxy cortisol 73 . The therapeutic bile acid ursodeoxycholic acid (UDCA) had no relevant effect on CYP3A metabolic activity 72,73 , but increased expression of the hepatocyte transporters BSEP, MDR3, and MRP4 by posttranscriptional mechanisms 72 .…”
Section: Pxr Agonistsmentioning
confidence: 71%
“…Consistent with this, Dilger et al showed that in patients with early stage PBC and healthy controls, rifampicin markedly induced CYP3A metabolism as assessed by pharmacokinetic profiling of budesonide and its phase 1 metabolites in plasma and urine and urinary 6β-hydroxy cortisol 73 . The therapeutic bile acid ursodeoxycholic acid (UDCA) had no relevant effect on CYP3A metabolic activity 72,73 , but increased expression of the hepatocyte transporters BSEP, MDR3, and MRP4 by posttranscriptional mechanisms 72 . These complementary effects on transcriptional regulation of hepatobiliary enzymes and transporters suggest that the combined use of both agents might have synergistic beneficial effects in patients with non-obstructive cholestasis.…”
Section: Pxr Agonistsmentioning
confidence: 71%